2011
DOI: 10.2308/accr-10164
|View full text |Cite
|
Sign up to set email alerts
|

Compensation Committees' Treatment of Earnings Components in CEOs' Terminal Years

Abstract: Compensation committees face special difficulties when setting pay in the last years of a CEO's tenure. For example, incentives to manipulate earnings for the purpose of enhancing earnings-based compensation are greater in CEOs' terminal years. We predict that compensation committees are aware of these incentives and adjust the relative weights placed on earnings components in the cash compensation function to mitigate the problem. Consistent with our prediction, we find that in CEOs' terminal years, positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 52 publications
1
41
0
Order By: Relevance
“…Because a CEO's compensation is generally comprised of a cash component (salary plus bonus) and a stock-based component (options plus restricted stock), we focus on these two components in separate regression analyses. Our methodological approah is similar to prior work that provides evidence on relation between CEO compensation and various earnings components in other contexts such as Dechow, Huson & Sloan (1994); Gaver & Gaver (1998); Comprix & Muller (2006); and Huson, Tian, Wiedman & Wier (2012). Our baseline regression model provides several interesting results.…”
Section: Introductionsupporting
confidence: 55%
“…Because a CEO's compensation is generally comprised of a cash component (salary plus bonus) and a stock-based component (options plus restricted stock), we focus on these two components in separate regression analyses. Our methodological approah is similar to prior work that provides evidence on relation between CEO compensation and various earnings components in other contexts such as Dechow, Huson & Sloan (1994); Gaver & Gaver (1998); Comprix & Muller (2006); and Huson, Tian, Wiedman & Wier (2012). Our baseline regression model provides several interesting results.…”
Section: Introductionsupporting
confidence: 55%
“…As a CEO approaches retirement, the incentive for myopic behavior increases (Kalyta 2009). The literature on the horizon problem has shown that, to mitigate the retiring CEO's horizon problem, boards treat executive compensation differently when a CEO is close to retirement (Cheng 2004;Huson et al 2012). Similarly, the board's choice of ratchet parameters may differ when the CEO is close to retirement.…”
Section: Hypothesis 2c: Ceo Horizons and Target Ratchetingmentioning
confidence: 99%
“…De Jong, Mertens, van der Poel, and van Dijk (2012) report that also analysts recognize a benefit of smooth earnings, although they dislike earnings smoothing if it reduces transparency.11 Huson, Tian, Wiedman, and Wier (2012) provide empirical evidence that compensation committees adjust the weights in the variable compensation in the final year of a CEO to counter the CEO's greater incentives for earnings-increasing manipulation.12 The reason that the horizon effect only indirectly affects the first-period earnings management is that the bias in the second period is more extreme and unrelated to the manager's nonfinancial information, which is anticipated in the first-period earnings management decision. Increasing the tenure of managers would, therefore, not qualitatively affect our results derived for the first period.Forward-Looking Accounting Standards 7 Downloaded by [New York University] at 09:03 03 June 2015…”
mentioning
confidence: 96%